PENINGKATAN MINAT BACA GENERASI SEKOLAH MELALUI PENDIRIAN PERPUSTAKAAN ALAM KANAL SUKO-SUKO DI DESA SUKOREJO - Aprillianto, Bayu; Marshelina, Riska; Qomaria, Firzanah Yahya; Kholidah, Amilatul; Ilannajah, Annufus; Musi, Mardiajeng Pawestri; Wulandari, Novi; Purnamawati, Indah (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) Universitas Panca Marga Probolinggo, 2024)
Sukorejo Village is one of the villages in Jember Regency, where the reading interest among school-aged children remains low. Reflecting the common challenges faced by the younger generation today, Sukorejo Village requires concrete efforts to foster a reading culture, enabling the youth to perceive books as gateways to the world, thereby enhancing their knowledge and insights. Sukorejo Village features a tourist attraction known as the